Students’ Perceptions on Reading Activities at Interpretive Reading and Argumentative Writing Class at English Education Department Universitas Muhammadiyah Yogyakarta - Puji Astutik (PBI 15 UMY 044, 2015)
*44 Reading is an important life skill that will help you to work and learn independently. The purpose of this study was to explore and describe the students’ perceptions about the reading activities at Interpretive Reading and Argumentative Writing class. The other purpose was to explore and describe the activities applied by the lecturer at Interpretive Reading and Argumentative Writing class. The method used in this research was qualitative. The setting of this study was in English Education Department, Faculty of Language Education at Universitas Muhammadiyah Yogyakarta. The participants were five students of English Education Department batch 2014 and two lecturers who taught the class. The instrument and the technique of data collection of this research was interviews. The findings of this research revealed students perception of the activities: pre-reading, while-reading, and post-reading. The students felt enjoy and helpful in the learning process of reading activities in the class. In addition, the students had opinions that the reading activities gave several benefits, such as the students felt their vocabularies built, the students felt more confident and knowledgeable, the students felt their creativities improved, and the last is the students felt their writing skill improved.